Digital Men and Social Media: Unpacking the Reasons Behind Scrolling - Latif, Alfa Taufan; Jawahir, Moh (Jurnal Studi Ilmu Sosial dan Politik, 2025)
Purpose: This study explores the underlying motivations of male digital users in Indonesia for using social media platforms, particularly focusing on the interplay between entertainment, religious learning, social connection, information-seeking, and self-expression. The research aims to understand how cultural and religious contexts influence digital engagement among this demographic group. Methodology/approach: A qualitative phenomenological approach was employed, involving in-depth interviews with 25 male social media users aged 18–30. Data were collected through semi-structured interviews and analyzed thematically using an inductive method. Techniques such as member checking and peer debriefing were applied to enhance credibility. Results/findings: The findings reveal five overlapping motivations: (1) entertainment as emotional regulation and habit-forming behavior; (2) religious learning as spiritual reinforcement and identity expression; (3) social connection through online brotherhood and niche communities; (4) information-seeking driven by curiosity and personal growth; and (5) self-expression as a means of moral signaling and personal branding. These motivations are mediated by gender norms, religious values, and platform affordances. Conclusions: Male digital users strategically utilize social media to fulfill emotional, spiritual, social, intellectual, and expressive needs. This behavior highlights the integration of technology with masculine identity and Islamic values in a digital context. Limitations: The study is limited to urban settings in Java and focuses on a specific age group. It does not include platform usage logs or cross-platform comparisons. Contribution: This research contributes to media and communication studies by offering a culturally grounded understanding of male digital behavior, expanding on Uses and Gratifications Theory (UGT), Self-Determination Theory (SDT), and Social Identity Theory (SIT) in non-Western contexts.